Prioritisation in Service Allocation for Older People With Mental Health and/or Substance Use Disorders: Healthcare Providers’ Perspectives in Norway - Marte Lilløy Aabø (Nordisk Välfärdsforskning)
Background: Older people with mental health and/or substance use disorders (MH/SUDs) have received little attention from care researchers. Inadequate attention increases the risk of older vulnerable individuals not receiving essential services. Aim: To explore primary healthcare providers’ perspectives on why services for older people with MH/SUDs are not prioritised and how this is legitimised. Design and method: This research draws on semi-structured interviews conducted in a medium-sized Norwegian municipality. The empirical material comprises eight individual interviews with healthcare providers from a home care service unit and a mental health and substance abuse unit. Findings: This study reveals two primary findings. First, a clear distinction is observed between somatic and mental needs. The home care service primarily prioritises patients with somatic needs, which healthcare providers legitimise by stating they lack the right competence on MH/SUD. Somatic needs often take precedence over addressing MH/SUD needs. Second, younger people with MH/SUD are often prioritised over older people. This is legitimised by a perception that it would be beneficial to prioritise younger people. Conclusions: Despite the universalistic nature of the Norwegian welfare state by law, the findings indicate that older people with MH/SUDs receive fewer MH/SUD services than younger people when service allocation is considered. Older people with MH/SUD end up receiving services primarily addressing somatic needs from the HCS rather than services from the MH/SUD unit.